Kawasan Perbukitan Gunung Wungkal di Kabupaten Sleman: Kajian Arkeologi Lanskap - Prastyanto, Yulvian; Yuwono, J. Susetyo Edy (Department of Archaeology, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2023)
The hilly area of Gunung Wungkal, with its fluvial-volcanic plains and denudational hill landforms, has a relatively compound historical-culture in the form of archaeological, historical, and ethnographic potentials. This research is aimed to identify the archaeological, historical, and ethnographic potentials in the area and the formation of the archeological landscape. Quantum-GIS mapping software was applied to spatially analyze the intended area. This research shows that the hilly landscape of the Gunung Wungkal has been spatio-temporally shaped by the occurrence of archaeological remains, historic events, ethnographic perception, as well as the characteristic of local geomorphology. Two landform units are recognized to have different roles. The denudational hills landform is used as a sacred space, while the fluvial-volcanic plains is functioned as communal spaces. In addition, water springs are an important factor of the landscape that greatly influences the formation of the community landscape. Apart from being natural resources, they are also cultural resources that give rise to myths and legends. === Kawasan perbukitan Gunung Wungkal memiliki bentuk lahan berupa dataran fluvio-vulkanik dan perbukitan denudasional. Kawasan ini mempunyai kronik budaya berupa potensi arkeologi, sejarah, dan etnografi. Penelitian ini bertujuan untuk mengetahui potensi arkeologi, sejarah, dan etnografi pada masing-masing unit bentuk lahan dan bagaimana karakter lanskap yang terbentuk di Kawasan Perbukitan Gunung Wungkal menggunakan pendekatan arkeologi lanskap. Pengolahan data dilakukan menggunakan perangkat lunak (software) Quantum GIS (QGIS). Hasil penelitian menunjukkan bahwa lanskap arkeologi yang ada di Kawasan Perbukitan Gunung Wungkal, secara spatio-temporal dibentuk oleh potensi arkeologi lintas periode, sejarah, etnografi, dan kondisi bentang lahan setempat. Bentuk lahan perbukitan denudasional dimanfaatkan menjadi ruang yang bersifat sakral dan dataran fluvio-vulkanik menjadi ruang yang bersifat komunal. Hasil lain menunjukkan bahwa mata air merupakan unsur bentang lahan yang banyak mempengaruhi perkembangan lanskap masyarakat, yaitu sebagai lokus atas kemunculan mitos dan legenda.